2003
DOI: 10.1002/cncr.11266
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic role of tumor suppressor gene PTEN/MMAC1/TEP1 in hepatocellular carcinoma

Abstract: BACKGROUND Inactivation of the tumor suppressor gene PTEN/MMAC1/TEP1, located on chromosome 10q23, is a common event in advanced stages of diverse human malignancies. However, the prognostic role of PTEN expression in patients with hepatocellular carcinoma (HCC) has not been characterized. METHODS One hundred five resected specimens were collected from patients with HCC. Expression levels of PTEN and p53 in clinical samples were analyzed by immunohistochemistry. RESULTS Immunohistochemical analysis of 105 HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
188
3
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 266 publications
(207 citation statements)
references
References 32 publications
9
188
3
7
Order By: Relevance
“…Receptor tyrosine kinase activation rather than somatic mutations of PTEN or PI3KCA, which are rare in HCC, is likely to be responsible for activation of mTOR in HCC. Consistent with this notion, activation of AKT has been found in 40%-60% of human HCC samples (12) and is a risk factor for early recurrence and poor prognosis (13). More importantly, recent studies using knockout mice showed that mTOR activation was sufficient to cause HCC in rodent models (14), indicating the pivotal role of mTOR signaling in HCC.…”
Section: Introductionmentioning
confidence: 79%
“…Receptor tyrosine kinase activation rather than somatic mutations of PTEN or PI3KCA, which are rare in HCC, is likely to be responsible for activation of mTOR in HCC. Consistent with this notion, activation of AKT has been found in 40%-60% of human HCC samples (12) and is a risk factor for early recurrence and poor prognosis (13). More importantly, recent studies using knockout mice showed that mTOR activation was sufficient to cause HCC in rodent models (14), indicating the pivotal role of mTOR signaling in HCC.…”
Section: Introductionmentioning
confidence: 79%
“…22 Moreover, decreased PTEN correlates with tumor progression and poor prognosis in HCC. 20,23 Loss of functional PTEN leads to increased activity of AKT and the mammalian target of rapamycin (mTOR) kinase pathways, which can promote both cell survival and proliferation through phosphorylation and inactivation of several downstream mediators. 24 Activation of FAK has been observed in human HCC, and an increase in FAK activity correlates with more aggressive tumor behavior.…”
Section: Discussionmentioning
confidence: 99%
“…18 The closing date of follow-up was December 31, 2002. All the HCC specimens consisted of paired tumor and adjacent nontumor parts.…”
Section: Hcc Specimensmentioning
confidence: 99%
“…The stages of HCC were classified according to the staging system by the International Union against Cancer with slight modification as described previously. 18 The hepatic fibrosis stages in nontumor tissues were determined by masson trichrome staining and divided into three groups for comparison: group 1 (fibrosis 0-1), group 2 (fibrosis 2-3), and group 3 (fibrosis 4: cirrhosis).…”
Section: Hcc Specimensmentioning
confidence: 99%
See 1 more Smart Citation